STUDI PENGETAHUAN LOKAL MASYARAKAT MOYA TENTANG PEMANFAATAN TUMBUHAN SEBAGAI OBAT TRADISIONAL - Hartono Pitra; Ade Haerullah; Nurmaya Papuangan (SAINTIFIK@, 2017)
The objective of this research is concerning utilization of traditional medicinal plants to know society know ledge and parts of medicinal plants that is utilized as medicinal traditional as Ethnobotany study at society of Kelurahan Moya of Ternate Central. This research was conducted at Kelurahan Moya of Ternate Central on November to December 2015. Data collecting in this research used observation method, participation, deeply interview and documentation. The data was analyzed by using qualitative descriptive. The result of this research shows that society knowledge concerning medicinal plants is obtained hereditary and experience, as many as 27 species of medicinal plants are used as traditional medicine, which spread in 19 familiae included Malvaceae 14.8 %, Acanthaceae 7.40%, Apiaceae 7.40%, Cactaceae 7.40%, Euphorbiaceae 7.40%, Rubiaceae 7.40%, Zingiberaceae 7.40%, Arecaceae 3.70%, Fabaceae 3.70%, Lamiaceae 3.70 %, Liliaceae 3.70%, Meliaceae 3.70%, Myristicaceae 3.70%, Poaceae 3,70%, Piperaceae 3,70%,Punicaceae 3.70%, Syrtaceae 3.70 %, Myrtaceae 3.70 % and Annonaceae 3.70 %. Part used as medicinal includes 70.3% leaves, 11.1% fruit, 7.40% sap, 7,40%rhizome, 3.7% root, and 3.70% tuber. Leaf is an organ of the plant most widely used as a traditional medicinal because generally leaf is soft structured, it has a high water content (79-80%), besides as accumulation of photosynthesis that contains elements that have many benefits for treatment. Moya Society knowledge about medicinal plants is obtained by hereditary and through treatment experience.Key words: Ethnobotany, medicinal plant, kelurahan Moya, medicinal tradisional